Critical thinking assessment in the teaching of writing Indonesian scientific texts in high school - Rustam, Rustam; Priyanto, Priyanto (Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
The assessment of critical thinking in the teaching of Bahasa Indonesia is an essential part of teaching syntax because most Bahasa Indonesia teachers of high schools in Jambi still use objective test assessments or low-order thinking skills (LOTS). In fact, there are still many Bahasa Indonesia teachers of high schools in Jambi who have not implemented HOTS-based assessment, so the teaching process and learning outcomes of writing HOTS-based scientific texts are still low. To overcome this problem, it is necessary to study the critical thinking assessments in writing Indonesian scientific texts in high school to find authentic and contextual assessment designs to achieve learning objectives. The research method used is a mixed method of the concurrent embedded design. The qualitative data were collected through interviews, observation, and documentation, while the quantitative data were collected by using an essay test. The results of the study indicate that Indonesian language teachers have designed critical thinking assessments in writing scientific texts by conducting basic competency (BC) analysis, analyzing competency achievement indicators (CAI) by considering action verbs (AV), making stimuli, making question grids, constructing question criteria, and scoring by considering critical thinking aspects, including (1) focus, (2) supporting reasons, (3) organization, (4) conventions, and (5) integration. Student learning outcomes in writing scientific texts show good critical thinking competence in accordance with learning objectives.